Oligopsony and Minimum Wages (2021)
This article presents a model of oligopsony. It considers different conjectural variations that cover the whole range between the extreme cases of monopsony and perfect competition, such as Collusion, Threat, Cournot, Stackelberg, and Bertrand, and compares them in terms of prices, quantities, profits, mark-down, price elasticity of supply and welfare. It also considers the impact of minimum wages, under the different conjectures analyzed.